Correspondencia entre Antonio Vázquez, Mateo Rodríguez y Roberto H. Todd - Vázquez, Antonio; Rodríguez, Mateo; Todd, Roberto H. (My University, 1936)
Rescate de los libros de Mariano Abril
Keywords: Abril Ostalo, Mariano, 1861-1935